Reminders of Mortality Alter Pain-Evoked Potentials in a Chinese Sample - Wang, Chenbo; Tian, Jing (Frontiers in Psychology, 2018)
Pain is of evolutionary importance to human survival. However, the perception of pain could be changed when death-related thoughts are accessible. Although the influence of mortality salience on pain processing has been investigated in Westerners recently, it is unclear whether this effect is constrained by specific culture context since humans may employ cultural worldviews to defend the existence problem. The current study tested whether and how mortality salience affects pain processing in a Chinese male sample. We primed participants with sentences indicating mortality salience or negative affect on either of two days. Both before and after the priming, event-related potentials (ERP) elicited by painful and non-painful electrical stimulations were recorded. Results showed that pain-evoked potentials were identified as an early negative complex N60-P90-N130 and a late positivity P260. Pain-evoked N130 after mortality salience priming was larger than that after negative affect priming. Meanwhile, pain-evoked P260 decreased after mortality salience priming but not after negative affect priming. These findings indicate that reminders of mortality affect both early sensory and late cognitive neural responses related to physical pain. As previous studies reporting an increased effect of mortality salience on perceived pain intensity in Westerners, we found an unchanged or possibly reduced effect in Chinese. Thus, the current work provides insight into a culture-sensitive perspective on how pain processing would be modulated when existential problem occurs.